Location Management Cost Reduction Using Adaptive Velocity-Movement Based Scheme In Personal Cellular Networks (Pcn) - Elgembari, Mabruk Saleh M (2002)
Wireless personal communication networks (PCNs) consist of a fixed wireless network with nodes providing wireless coverage area and a large number of mobile terminals (MTs). These terminals are free to travel within the PCN coverage area without service interruption. Each terminal periodically reports its location to the network by a process called location update. When a call arrives for a particular mobile terminal, the network will determine the exact location of the destination terminal by a process called terminal paging. There are many schemes proposed which aim at reducing signaling costs and all these schemes were based on different assumptions and network parameters. Our objective is to study the updating and paging process of the MTs under different dynamic location management schemes, and to develop an adaptive scheme that caters for the ever-changing network parameters. In this thesis, a dynamic paging scheme is proposed and presented based on the semi-real time velocity information of an individual mobile user. This allows for more accurate prediction of the user location when a call arrives and therefore, reducing the cost of paging. The scheme is based on a basic scheme that was proposed in the open literature. Our new scheme results show that the newly proposed adaptive movement threshold and the adaptive velocity time unit schemes provide significant costs savings, compared to a benchmark system and the basic scheme, under different cell radius sizes and MT velocities broadly classified as high and low mobility systems.